2016
DOI: 10.1104/pp.16.00990
|View full text |Cite
|
Sign up to set email alerts
|

In planta localization of stilbenes within Picea abies phloem

Abstract: Phenolic stilbene glucosides (astringin, isorhapontin, and piceid) and their aglycons commonly accumulate in the phloem of Norway spruce (Picea abies). However, current knowledge about the localization and accumulation of stilbenes within plant tissues and cells remains limited. Here, we used an innovative combination of novel microanalytical techniques to evaluate stilbenes in a frozen-hydrated condition (i.e. in planta) and a freeze-dried condition across phloem tissues. Semiquantitative time-of-flight secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 41 publications
1
34
0
1
Order By: Relevance
“…The reasons for the observed decline in the content of stilbene glycosides and aglycones in Norway spruce bark may include trans to cis - isomerization of the double bond and subsequent photocyclization reactions, as stilbenes are well-known for their reactivity and photosensitivity [ 9 , 17 ]. The stilbene compounds may also leach out, as they are water soluble and mostly located within the soft tissue layers of inner bark [ 18 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for the observed decline in the content of stilbene glycosides and aglycones in Norway spruce bark may include trans to cis - isomerization of the double bond and subsequent photocyclization reactions, as stilbenes are well-known for their reactivity and photosensitivity [ 9 , 17 ]. The stilbene compounds may also leach out, as they are water soluble and mostly located within the soft tissue layers of inner bark [ 18 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Evidence exists that the content and composition of bark metabolites varies within bark layers, between individual trees and forest stands, as well as among the geographical origins of tree populations [ 18 , 19 , 20 ]. These biological variations in bark quality may, however, be rapidly exceeded by the more pronounced property changes due to terminal and logistical operations, e.g., storage of biomass [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pan et al (2009) also noted that the STS protein localization did not considerably change during berry development. Recently, Jyske et al (2015Jyske et al ( , 2016) applied a combination of novel microanalytical techniques to analyze distribution and localization of stilbenes in a frozen-hydrated condition (i.e., in planta) across phloem tissues of Norway spruce Picea abies and found that stilbenes were localized in axial parenchyma cells.…”
Section: Stilbene Distribution Contents and Localizationmentioning
confidence: 99%
“…Previously, the role of syringin as a phenolic glucoside compound stored in the phloem region was discussed in connection with its defensive characteristics (Cis, Nowak, & Kisiel, 2006;Cipollini et al, 2011). Similar compounds such as stilbene glucosides were also reported as defensive compounds, and their distribution in the phloem region was studied in detail (Jyske et al, 2016).…”
mentioning
confidence: 99%